Catálogo revisado y anotado de las Orchidaceae de Costa Rica - Pupulin, Franco (2016)
A c o m p l e t e c o m p i l a t i o n o f a l l c u r r e n t l y r e c o g n i z e d s p e c i e s o f o r c h i d s ( O r c h i d a c e a e ) k n o w n f r o m Costa Rica, and documented by a voucher specimen cited in the text, is presented. Species are listed in alphabeti- cal order. For each especies the accepted synonyms and species names used in older treatments are included, together with bibliographical references. For some of the critical taxa brief taxonomic observations are given. The synopsis includes 1360 species in 180 genera, of which 287 species are recently described or were not reported in earlier studies. The species endemic to Costa Rica represent 26% of the reported species. The new combination Echinella vittata and the new name Stelis megachlamys are proposed.